(untitled) (TAMADDUN NURI JURNALI, 2025)
This article describes the rights and freedoms of women and girls from history, the legal consciousness of women, and their level of social activity. It describes how women’s rights have developed from history, how they have been able to use these rights, how they have gained importance, and what similarities they have with women’s rights today. It specifically emphasizes the opportunities these rights have given women from history. This article discusses the history and development processes of women’s rights.